The relationship between Birth Order and Sales Person’s performance in Ghana. (International Journal of Technology and Management Research, 2020)
AbstractsThe aim of the study is to predict the impact of birth order effect on sales person’s performance. The main objective is to investigate the relationship between birth order; (firstborns, middle children, lastborns, and only children) on sales person’s performance. Besides, it also aimed to examine the relationship between personality and sales person’s performance. The target population of the study comprised of sales person’s shared mean age of 21.0 years (Standard Deviation= 1.93) and have worked as sales person for a minimum of three years. Participants were recruited from the Greater Accra Region of Ghana. The study adopted purposive sampling technique to select the sales person and a total of 788 out of the 900 participants returned their questionnaires. A linear regression equation was employed to measure how birth order predicts sales person’s performance, with birth order (firstborns, middle children, lastborns, and only children) as the predictor variables and sales person’s performance as the criterion variable. Results indicated that a participant of different birth positions does not differ significantly in terms of sales person’s performance.Keywords; Birth Order; sales person’s Performance; firstborn; Extraversion; Middle children